Determinant Factor of Small Medium Enterprises to Access Bank Credit - Eliada Herwiyanti; Ascaryan Rafinda (Universitas Pendidikan Ganesha, 2021)
This study aims to identify the determinant factors of bank credit access to small and medium enterprises. As the country's economy's backbone, the facts do not make SMEs free from capital constraints. Although the Government of Indonesia has issued a policy regarding lending through financial institutions, it turns out that this support has not played a significant role in encouraging SMEs to obtain bank credit. This research was conducted in Banyumas Regency, with the research respondents being SMEs who had already received credit. The study results found that financial literacy, credit terms, and quality information accounting affect bank credit access. It is concluded that limited access to bank credit can be improved if SMEs understand financial literacy, credit requirements, and accounting information quality.